2017
DOI: 10.1177/2192568217699185
|View full text |Cite
|
Sign up to set email alerts
|

Short Posterior Stabilization in Combination With Cement Augmentation for the Treatment of Thoracolumbar Fractures and the Effects of Implant Removal

Abstract: Study Design:Retrospective case series.Objective:Short posterior stabilization with vertebroplasty is one treatment option for thoracolumbar burst fractures (AO A3). Whether it avoids progression in segmental kyphosis, especially after implant removal, is unclear. In a retrospective case-control study, its stability and the effect on intervertebral discs with and without implant removal was studied.Methods:Fifty-nine consecutive patients were treated with bisegmental short posterior instrumentation and additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…This is a notable finding given the routine removal of implants following surgical stabilization with or without arthrodesis has previously remained controversial. 3,4,45 It is vital to recognize that our study deliberately excluded the cohort of overtly symptomatic patients, such as those with pain or disability, related to infection or hardware failure. Stavridis et al have already observed markedly improved pain scores following instrumentation removal in these circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a notable finding given the routine removal of implants following surgical stabilization with or without arthrodesis has previously remained controversial. 3,4,45 It is vital to recognize that our study deliberately excluded the cohort of overtly symptomatic patients, such as those with pain or disability, related to infection or hardware failure. Stavridis et al have already observed markedly improved pain scores following instrumentation removal in these circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…This is a notable finding given the routine removal of implants following surgical stabilization with or without arthrodesis has previously remained controversial. 3 , 4 , 45 …”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated by Figure , the T10 fracture is associated with the almost complete destruction of the anterior one‐third of the vertebral body. Although some may argue that cement augmentation should be reserved for osteoporotic fractures, there is an extensive literature, albeit mostly of retrospective nature, supporting the role of such therapeutic alternative in traumatic fractures …”
Section: Case Presentationmentioning
confidence: 99%
“…Although some may argue that cement augmentation should be reserved for osteoporotic fractures, there is an extensive literature, albeit mostly of retrospective nature, supporting the role of such therapeutic alternative in traumatic fractures. 4,5 Ultimately, because of the comminuted pattern of the T10 burst fracture and the multilevel nature of the injuries, the patient was offered the option of proceeding with a minimally invasive navigation-guided T8 to L1 posterior screw and rod fixation and T10, T11, and L2 kyphoplasties. After placement of the screws, the kyphoplasties were conducted ( Figure 3).…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation